La Gestión Emocional y el Comportamiento Social en el Subnivel Inicial II de la Escuela de Educación Básica San Felipe Neri, Ciudad de Riobamba - Molina Arroba, Melany Paola (2025)
The present research aims to strengthen social behavior through the implementation of emotional management strategies in children enrolled in Initial Level 2 at the Escuela de Educación Básica San Felipe Neri. A field study was conducted, as the research took place within the classroom setting, and it was descriptive in nature, given that it allowed for the identification and analysis of the various elements surrounding the problem. A mixed-methods approach was used: qualitative research based on observation and quantitative research supported by survey data tabulation. The initial results showed that 60% of the students knew what emotions are, 35% expressed themselves without aggression toward their peers and teachers, and 40% were able to regulate their emotions with adult assistance. After implementing strategies such as breathing based relaxation techniques, an “emotions corner,” among others, the students reached 85% in emotion identification, 65% in reduced aggression, and 70% in emotional regulation with teacher support. Empathy was also fostered, improving students’ emotional management despite a high rate of absenteeism, which limits the teaching–learning process.